POTENTIAL USE OF ENDOPHYTIC BACTERIA TO CONTROL Pratylenchus brachyurus ON PATCHOULI - Rita Harni; Supramana Supramana; Supriadi Supriadi (Indonesian Agency for Agricultural Research and Development, 2012)
Pratylenchus brachyurus is an important parasitic nematode which significantly decreases quality and quantity of patchouli oil. One potential measure for controlling the nematode is by using endophytic bacteria. These bacteria also induce plant growth. This study aimed to evaluate the potential of endo-phytic bacteria to control P. brachyurus. The experiments were carried out in the Bacteriological Laboratory of the Plant Protection Department, Bogor Agricultural University, and the Laboratory and Greenhouse of the Indonesian Spice and Medicinal Crops Research Institute from April to December 2007. Endophytic bacteria were isolated from the roots of patchouli plants sampled from various locations in West Java. Antagonistic activity of the isolates were selected against P. brachyurus and their abilities to induce plant growth of patch-ouli plants. Isolates having ability to control P. brachyurus and promote plant growth were identified by molecular techniques using 16S rRNA universal primers. The results showed that a total of 257 isolates of endophytic bacteria were obtained from patchouli roots and their population density varied from 2.3 x 102 to 6.0 x 105 cfu g-1 fresh root. As many as 60 isolates (23.34%) were antagonistic against P. brachyurus causing 70-100% mortality of the namatode, 72 isolates (28.01%) stimu-lated plant growth, 32 isolates (12.47%) inhibited plant growth, and 93 isolates (36.18%) were neutral. Based on their antago-nistic and plant growth enhancer characters, five isolates of the bacteria, namely Achromobacter xylosoxidans TT2, Alcaligenes faecalis NJ16, Pseudomonas putida EH11, Bacillus cereus MSK, and Bacillus subtilis NJ57 suppressed 74.0-81.6% nema-tode population and increased 46.97-86.79% plant growth. The study implies that the endophytic bacteria isolated from patchouly roots are good candidates for controlling P. brachyurus on patchouly plants. Bahasa IndonesiaPratylenchus brachyurus adalah nematoda parasit pada tana-man nilam yang dapat menurunkan hasil dan kualitas minyak nilam. Salah satu cara pengendalian yang potensial terhadap nematoda tersebut adalah menggunakan bakteri endofit. Selain dapat membunuh nematoda, bakteri endofit juga dapat meng-induksi pertumbuhan tanaman. Penelitian bertujuan untuk mengevaluasi potensi bakteri endofit yang berasal dari tanaman nilam untuk mengendalikan namatoda parasit P. brachyurus. Penelitian dilakukan di Laboratorium Bakteriologi, Departemen Proteksi Tanaman, Institut Pertanian Bogor, serta di laboratorium dan rumah kaca Balai Penelitian Tanaman Rempah dan Obat, pada bulan April sampai Desember 2007. Bakteri endofit diisolasi dari sampel akar tanaman nilam dari beberapa lokasi di Jawa Barat. Isolat-isolat bakteri endofit diseleksi kemampuannya untuk membunuh P. brachyurus dan menginduksi pertumbuhan tanam-an nilam. Isolat bakteri endofit yang potensial selanjutnya diidentifikasi secara molekuler menggunakan primer universal 16S rRNA. Penelitian memperoleh 257 isolat bakteri endofit dengan kerapatan populasi 2,3 x 102 sampai 6,0 x 105 cfu g-1 berat basah akar. Enam puluh isolat (23,34%) di antaranya bersifat antagonis terhadap P. brachyurus dengan mortalitas 70-100%, 72 isolat (28,01%) dapat memacu pertumbuhan tanaman nilam, 93 isolat (36,18%) bersifat netral, dan 32 isolat (12,47%) dapat menghambat pertumbuhan tanaman. Berdasarkan hasil peng-ujian antagonis dan pemacu pertumbuhan tanaman, lima isolat bakteri, yaitu Achromobacter xylosoxidans TT2, Alcaligenes faecalis NJ16, Pseudomonas putida EH11, Bacillus cereus MSK, dan Bacillus subtilis NJ57 dapat menekan populasi nematoda 74,0-81,6% dan meningkatkan pertumbuhan nilam 46,97-86,79%. Penelitian mengindikasikan bahwa bakteri endofit dari tanaman nilam berpotensi mengendalikan P. brachyurus pada tanaman nilam.